2022
DOI: 10.1055/a-1793-9508
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of post-ERCP pancreatitis by post-procedure amylase and lipase levels: A systematic review and meta-analysis

Abstract: Background and study aims Post-ERCP pancreatitis (PEP) is the most common complication attributed to the procedure, its incidence being approximately 9.7 %. Numerous studies have evaluated the predictive efficacy of post-procedure serum amylase and lipase levels but with varied procedure-to-test time intervals and cut-off values. The aim of this meta-analysis was to present pooled data from available studies to compare the predictive accuracies of serum amylase and lipase for PEP. Patients and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The determination of PEP can be challenging, as many studies fail to discern whether they considered post-procedure pain and pancreatic enzyme elevation to be expected outcomes of pancreatic duct visualization (9). This is further confounded by the fact that pediatric ERCPs are increasingly performed in the outpatient setting, where the timing of serum amylase/lipase levels can vary from 2 to 24 hours after ERCP in symptomatic patients (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The determination of PEP can be challenging, as many studies fail to discern whether they considered post-procedure pain and pancreatic enzyme elevation to be expected outcomes of pancreatic duct visualization (9). This is further confounded by the fact that pediatric ERCPs are increasingly performed in the outpatient setting, where the timing of serum amylase/lipase levels can vary from 2 to 24 hours after ERCP in symptomatic patients (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, blood tests have been used to predict pancreatic reactions after ERCP, but extensive studies have remained limited to amylase and lipase [ 5 , 6 , 7 ]. It has been found that some blood tests, which are not routinely collected, may also play a role in the occurrence of PEP-post-Endoscopic retrograde cholangiopancreatography pancreatitis [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these considerations, relatively little is known regarding the frequency with which alterations in biochemical and/or imaging parameters occur in asymptomatic patients following uncomplicated ERCP. Estimates of post-ERCP pancreatic enzyme increases within hours of the procedure are available [ 10 , 11 ], but estimates of the proportions of patients who experience alterations on routine measurement are scarce [ 12 ] and mainly confined to randomized trials, which may not represent real-world practices and generally do not have the ability to identify truly asymptomatic patients. Estimates of proportions of patients who are observed to have typical post-ERCP pancreatic imaging findings in the absence of adverse events are altogether absent.…”
Section: Introductionmentioning
confidence: 99%